Utilization of Pusdic Board Game in Increasing Level of Mastery of Grade 8 Learners in Predicting Phenotypic Expressions of Traits - Anselmo, Charlie T.; Opeña, Jeniffer L.; Delima, Precila C.; Balbin, Rhea P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigated the effectiveness of the Punnet Square Dihybrid Cross (PUSDIC) board game in enhancing Grade 8 students' mastery of predicting phenotypic expressions of traits. Using a quasi-experimental design with 40 students from Cauayan City National High School, the research compared an experimental group using the PUSDIC board game to a control group receiving traditional instruction. Results showed significantly higher post-test scores in the experimental group, with a mean increase of 28.10 points (p < .001) from pre- to post-test. The PUSDIC board game demonstrated a very large effect size, indicating its substantial impact on students' mastery of the subject. This interactive approach addresses challenges in teaching genetics by promoting active learning, critical thinking, and collaboration. The study supports the use of educational board games as an effective, accessible, and low-cost strategy for teaching complex scientific concepts to secondary school students, offering an engaging approach to improve science education outcomes.